Acrylamide-induced changes in femoral bone microstructure of mice - Sarocka, A; Babosova, R; Kovacova, V; Omelka, R; Semla, M; Kapusta, E; Goc, Z; Formicki, G; Martiniakova, M (Physiological research, 2017)
Acrylamide (AA) is one of the most common toxins in foods. Its effect on bone microstructure has not been investigated. The aim of our study was to analyze the impact of acute exposure to AA on femoral bone microstructure in mice. Adult animals were treated perorally with 2 doses of AA (E1 group, 1 mg/kg b.w.) in a 24-h period and with 3 doses of AA (E2 group, 1 mg/kg b.w.) in a 48-h period. Mice exposed to AA had smaller sizes of primary osteon's vascular canals. Secondary osteons were significantly smaller in mice from E2 group; however their increased number (from 38 % to 77 %) was identified in both E1 and E2 groups. In these groups, a higher number of resorption lacunae (from 100 % to 122 %) was also found. The values for bone volume, trabecular number were increased and that for trabecular separation was decreased in mice administered AA. Significantly higher value of bone surface was observed in mice from E1 group whereas trabecular thickness was increased in E2 group. The effect of AA on microstructure of compact and trabecular bone tissues is different. In our study, one dose of AA was used and acute effects of AA were investigated. Therefore, further studies are needed to study mechanisms by which AA acts on bone.
Keywords: trabekulární kostní tkáň; Animals; kortikální kost; femur; kontaminace potravin; zvířata; mužské pohlaví; rentgenová mikrotomografie; Male; Mice; X-Ray Microtomography; Cancellous Bone; Cortical Bone; Femur; Acrylamide; Food Contamination; akrylamid; myši